Determinants of malnutrition among the tea garden workers of Darjeeling district in 2021: an ordinal regression analysis - Mandal, Diptojyoti; Bhattacherjee, Sharmistha; Biswas, Asit Kumar; Samanta, Sampriti (International Journal Of Community Medicine And Public Health, 2023)
Background: Due to increasing lifestyle changes and poverty, double burden of malnutrition is becoming more and more severe, especially in the underserved areas like tea gardens. Food security is also a major issue not only in underdeveloped countries but also in developing countries like India. The study aims to estimate the prevalence of malnutrition among the tea garden workers and to find out the associated factors with malnutrition among the tea garden workers of Darjeeling district. Methods: 200 people were selected from 10 tea gardens of Darjeeling district by cluster sampling method. They were interviewed using a structured questionnaire to find out the associated factors with malnutrition. Weight and height was measured using standard measuring tools and then BMI was calculated. To find out the determinants of nutritional status, an ordinal regression analysis was done with the help of SPSS software. Results: The prevalence of under nutrition and obesity was 25% and 20.5% respectively. The ordinal regression model showed that the odds of higher BMI was found with increasing age, male gender, being a permanent garden employee and higher educational status. Household food insecurity increased the odds of undernutrition, as individuals from food secure households had significantly higher odds of getting higher BMI. Conclusions: Nutritional status is closely associated with socio-economic and demographical variables and household food security. To ensure the health and nutrition of the tea garden workers, a more comprehensive strategy to addressing socio-demographic issues and household food security is required.